Second Five Year Plan Punjab State Review of Progress for 1959-60 - Planning Commission (Planning Commission, 1959)
The economy of Punjab made a sustained advance during the year 1959-60 in several directions. Most of the major projects and schemes designed to bring about basic stability in the socio-economic life of the people of the State were implemented almost according to schedule, and there were only isolated exceptions. This shows that during the first four years of the Second Plan, the Punjab State utilized 71 per cent of the original outlay of Rs 162.68 crores and 75.7 per cent of the effective ceiling of Rs 152.51 crores.
The Planning Department Punjab State